2020
DOI: 10.1002/micr.30553
|View full text |Cite
|
Sign up to set email alerts
|

Limb‐salvage surgery with vascular reconstruction after lower extremity sarcoma resection: A systematic review and meta‐analysis

Abstract: Background Limb‐salvage surgery with vascular reconstruction is the current standard treatment when sarcoma involves major vessels of the lower extremity. However, the low incidence of sarcoma and rarity of limb‐salvage surgery are limiting factors for the reliable study of limb‐salvage surgery. Therefore, a systematic review was conducted to establish better management of lower extremity sarcoma based on currently available evidence. Methods A systematic review and meta‐analysis of data on limb‐salvage surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
4
20
0
Order By: Relevance
“…These findings are further bolstered by case–control studies by Ghert et al and Poultsides et al, which demonstrated comparable survival in patients with and without vascular involvement by sarcomas 4,7 including in retroperitoneal sarcoma resections 7 . While still controversial, vascular resection and reconstruction have been adopted in the surgical management of STS and other advanced pelvic tumors; however, no clear consensus exists regarding the indications and contraindications given the rarity of these presentations 13–15 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings are further bolstered by case–control studies by Ghert et al and Poultsides et al, which demonstrated comparable survival in patients with and without vascular involvement by sarcomas 4,7 including in retroperitoneal sarcoma resections 7 . While still controversial, vascular resection and reconstruction have been adopted in the surgical management of STS and other advanced pelvic tumors; however, no clear consensus exists regarding the indications and contraindications given the rarity of these presentations 13–15 …”
Section: Discussionmentioning
confidence: 97%
“…7 While still controversial, vascular resection and reconstruction have been adopted in the surgical management of STS and other advanced pelvic tumors; however, no clear consensus exists regarding the indications and contraindications given the rarity of these presentations. [13][14][15] In the present series, we report on our treatment experiences for nine patients, including five patients with locally advanced STS involving major arterial structures. To the best of our knowledge, our series is the first to report on short-and long-term outcomes among a diverse patient cohort with locally infiltrative tumors requiring multivisceral resection and complex/protracted previous oncologic histories.…”
Section: Discussionmentioning
confidence: 99%
“…Only one amputation was required in our nineteen-patient series. According to a recently published systematic review, including 271 patients that had limb-salvage sarcoma surgery with vessel reconstruction, the overall patency and amputation rates reported in the literature are 85% and 11%, respectively 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In the recent systematic review by Fujiki et al 20 for sarcoma patients requiring vessel reconstruction mortality rates were not analysed. However, the 5-year survival rate of 58% in our cohort, seems to be within the expected range for these kind of tumours 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve this, it is not uncommon that an inguinal orchiectomy must be performed, especially if tumours arise from para-testicular, scrotal or spermatic cord tissues 5 . Even though amputation of the lower extremity is sometimes unavoidable, a limb-preserving approach can provide satisfactory oncological outcomes while preserving form and function 6 . Soft tissue reconstruction is frequently indicated following tumour excision when primary closure is not possible, this allows for accelerated healing and rehabilitation 7 .…”
Section: Introductionmentioning
confidence: 99%